2019
DOI: 10.1002/tee.23001
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method Based on PPSO for Optimal Placement and Sizing of Distributed Generation

Abstract: Energy loss minimization, voltage profile improvement, and increasing reliability of the power system are the prominent advantages of distributed generation (DG) unit's integration in distribution systems. Therefore, optimal placement and sizing of DG become a critical issue. This article proposes a recently developed adaptive particle swarm optimization (PSO) algorithm known as phasor particle swarm optimization (PPSO) to solve the problem of optimal placement and sizing of DG units in radial distribution net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 33 publications
(43 reference statements)
0
10
0
4
Order By: Relevance
“…For more clarity on the decision variables, taking the example of the optimal power flow (OPF) [11,28]. Control variables control the power flow, while the state variables describe the power system state, such as: where PNG is the generated power at all generation buses except the slack bus, VNG is the voltage at generation buses, TSNT is the transformers tap-setting, and QNC is the shunt VAR compensators.…”
Section: Common Mathematical Rdgp's Problem Formulationmentioning
confidence: 99%
“…For more clarity on the decision variables, taking the example of the optimal power flow (OPF) [11,28]. Control variables control the power flow, while the state variables describe the power system state, such as: where PNG is the generated power at all generation buses except the slack bus, VNG is the voltage at generation buses, TSNT is the transformers tap-setting, and QNC is the shunt VAR compensators.…”
Section: Common Mathematical Rdgp's Problem Formulationmentioning
confidence: 99%
“…U literaturi se za rješavanje problema optimalne alokacije i snage obnovljivih izvora najčešće koriste brojni metaheuristički algoritmi: Particle Swarm Optimization (PSO) [3], Phasor Particle Swarm Optimization (PPSO) [4], Backtracking Search Optimization Algorithm (BSOA) [5], Augmented Lagrangian Genetic Algorithm (ALGA) [6], Ant Lion Optimization Algorithm (ALOA) [7], Particle Swarm Optimization with Constriction Factor Approach (PSOCFA) [8]. Neki autori predlažu primjenu kombinovanih, odnosno hibridnih metoda: hybrid PIPSO-SQP [9], kombinacija Genetic algorithm (GA) i Particle Swarm Optimization (PSO) [10], Binary Particle Swarm Optimization and Shuffled Frog Leap (BPSO-SLFA) [11], kombinacija Harmony Search Algorithm (HSA) i Particle Artificial Bee Colony Algorithm (PABCA) [12], Shuffle Bat Algorithm (ShBAT) [13].…”
Section: Uvodmentioning
confidence: 99%
“…Pored baznog slučaja proračun optimalnih tokova snaga je izveden za još 4 scenarija u kojima su priključivani: 1, 2, 3 i 6 obnovljivih izvora. Mjesta priključivanja i snage obnovljivih izvora preuzete su iz [4][5], [8][9] i [12]. Slika 3 -Naponi u čvorovima u slučaju sa i bez obnovljivih izvora Na slici 3 prikazani su naponi u čvorovima, dok na slici 4 padovi napona po granama, za slučaj sa i bez obnovljivih izvora.…”
Section: Simulacije I Rezultatiunclassified
See 1 more Smart Citation
“…Some literature concerns the optimal layout of distributed generators as follows. Ullah et al have suggested an analytical approach determine the optimum location and size of distributed generators using (PSO) and (PPSO) method to reduce losses and improve the voltage profile [7]. Montoya et al have proposed a general algebraic modeling system (GAMS) with a BONMIN solver in which the problem was diagnosed as a mixed-integer nonlinear programming (MINLP) to define the optimal location and size of DGs [3].…”
Section: Introductionmentioning
confidence: 99%